2015
DOI: 10.3389/fncel.2015.00315
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and excitatory axon terminals share a common nano-architecture of their Cav2.1 (P/Q-type) Ca2+ channels

Abstract: Tuning of the time course and strength of inhibitory and excitatory neurotransmitter release is fundamental for the precise operation of cortical network activity and is controlled by Ca2+ influx into presynaptic terminals through the high voltage-activated P/Q-type Ca2+ (Cav2.1) channels. Proper channel-mediated Ca2+-signaling critically depends on the topographical arrangement of the channels in the presynaptic membrane. Here, we used high-resolution SDS-digested freeze-fracture replica immunoelectron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 54 publications
(66 reference statements)
0
34
0
Order By: Relevance
“…Assuming that receptor density remains constant, as suggested by the finding of very high and homogenous AMPA receptor density at PF-MLI synapses (37) (30,31,33), we found that Ca v 2.1 channel labels were not distributed uniformly. The distribution of distances between any pair of particles within an AZ displayed a peak in the range between 0 nm and 50 nm (particularly evident in 4-wk data), indicating particle association within clusters, whereas beyond this range particle distances were distributed broadly ( Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 90%
See 1 more Smart Citation
“…Assuming that receptor density remains constant, as suggested by the finding of very high and homogenous AMPA receptor density at PF-MLI synapses (37) (30,31,33), we found that Ca v 2.1 channel labels were not distributed uniformly. The distribution of distances between any pair of particles within an AZ displayed a peak in the range between 0 nm and 50 nm (particularly evident in 4-wk data), indicating particle association within clusters, whereas beyond this range particle distances were distributed broadly ( Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 90%
“…To define a cluster, we set a threshold value of 40 nm for the distance between particles belonging to the same cluster. This value was calculated as equal to μ + 3σ, where μ and σ are the mean (18.7 nm) and SD (7.1 nm) obtained for a single Gaussian fit of a 2-wk nearest neighbor distance distribution; it is very close to the value of 42 nm used previously by Althof et al (30). Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 94%
“…This recording configuration is convenient because the ATP concentration is known and endogenous EF-hand mobile buffers have been dialyzed (Müller et al, 2007). The resting free [Ca 2ϩ ] was set to 50 nM, the Ca 2ϩ diffusion coefficient (D Ca ) to 220 m 2 /s (Allbritton et al, 1992), the endogenous fixed buffer (EFB) binding ratio to 40 (Helmchen et al, 1997), the EFB concentration to 4 mM, the EFB K D to 100 M, and an EFB forward binding rate constant (k on ) to 1 ϫ 10 8 M Ϫ1 sec Ϫ1 (Nakamura et al, 2015). We included 200 M free ATP in the simulation, assuming the presence of 2 mM ATP (total concentration) and 3 mM Mg 2ϩ (calculation using Maxchelator RRID:SCR_000459).…”
Section: Methodsmentioning
confidence: 99%
“…20,46,71,118 Investigations of the release probability, channel distribution, as well as evoked calcium signals, point to a clustered distribution of presynaptic calcium channels. 4,66,103 The distance of VGCC clusters and synaptic vesicles varies between different synapses 7,46,71,135 and implies different channel arrangements in the different synapses. 103,117 Bearing lateral diffusion in mind, several options for modulation of synaptic release probability and short-term plasticity emerge.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%